An autopsy case of pulmonary arterial hypertension in an elderly patient with multimorbidity: a case report. Issue 1 (28th December 2021) - Yokose, Masashi; Tomoe, Takashi; Yamaguchi, Takehiko; Yasu, Takanori
Abstract: Background: There is an increasing number of elderly patients with pulmonary arterial hypertension (PAH), and their characteristics differ from those of young or middle-aged patients with this condition. Case summary: A 73-year-old woman with a history of myocardial infarction and cardiovascular risk factors was admitted to the hospital with 2-week exertional dyspnoea. Her initial diagnosis was heart failure with preserved ejection fraction, but the symptoms persisted despite receiving treatment with diuretics. Additional tests showed a significant decrease in diffusing capacity of carbon monoxide and findings suggestive of severe pulmonary hypertension (PH). Contrast-enhanced computed tomography of the chest, and pulmonary angiography, showed no narrowing or obstruction of the pulmonary arteries. Right heart catheterization revealed haemodynamic data implying pre-capillary PH. Her condition gradually deteriorated to World Health Organization functional class IV, and sequential combination therapy with tadalafil, macitentan, and selexipag was initiated with a PAH diagnosis; however, she died 1 month later. Pathological findings in autopsy were consistent with PAH, and some parts of the lungs revealed the presence of obstructive and interstitial lung disease. Discussion: The majority of elderly patients with PAH might have multimorbidity. However, there is no specific treatment strategy. It is associated with diagnostic delay and worse prognosis; therefore, early suspicion and comprehensive tests, including right heart catheterization, are essential for better management.